Working Duration as a Risk Factor for Respiratory Symptoms among Traditional Compressor Divers in Soropia District, Konawe Regency (HEALTH CARE: JURNAL KESEHATAN, 2026)
Traditional compressor divers are at risk of respiratory health problems due to repeated exposure to hyperbaric environments and compressed air during diving activities. This study aimed to analyze the association between working duration and respiratory symptoms among traditional compressor divers in Soropia District, Konawe Regency. A cross-sectional study was conducted involving 57 divers selected using a total sampling technique. Data were collected using a structured questionnaire covering occupational characteristics and post-diving respiratory symptoms and analyzed using descriptive statistics and chi-square tests. Respiratory symptoms after diving were reported by 27 respondents (47.4%), while most respondents had worked as divers for more than five years (84.2%). A significant association was found between working duration and respiratory symptoms (p=0.044). Divers with more than five years of working duration were 9.45 times more likely to experience respiratory symptoms than those with five years or less (OR=9.45; 95%CI=1.10–81.58). Smoking history, diving duration, and diving frequency were not significantly associated with respiratory symptoms. Working duration as an indicator of cumulative occupational exposure may increase the risk of respiratory symptoms among traditional compressor divers. Periodic respiratory health monitoring and occupational health promotion are needed to prevent respiratory health problems in this population.